Single and Dual Task Gait Speed in Frailty Screening of Community-Dwelling Older Adults - Joey Yeo; Laura Tay; Yong Hao Pua; Shi Min Mah; Ee Ling Tay; Min Xian Wang; Yee Sien Ng (Journal of Primary Care & Community Health)
Objective: This study compares dual task (DT) gait speed between robust and frail older adults in the setting of a community-based frailty screening program. Methods: A cross-sectional study was conducted involving older adults aged 50 years or older. Participants were categorized as robust, pre-frail or frail using the FRAIL phenotype. Gait speed was measured under single task (ST) and 2 DT conditions: arithmetic (DT1) and verbal fluency (DT2) tasks. For the arithmetic task, participants counted upwards in multiples of 2, starting from 16. For the verbal fluency task, they named different animals as they walked. Results: A total of 976 participants were recruited, of which 779 were robust, 181 were pre-frail and 16 were frail. Robust participants exhibited significantly faster DT gait speeds (DT1: 1.12 (0.25)m/s; DT2: 0.97 (0.27)m/s than pre-frail/frail (PFF) participants (DT1: 0.88 (0.30)m/s); DT2: 0.78 (0.30)m/s). Robust participants also demonstrated a significantly faster ST gait speed (1.31 (0.22)m/s) vs 1.05 (0.31)m/s). Conclusion: DT gait assessment combines both physical and cognitive domains and may serve as a more holistic tool for early frailty detection in the community. The significant differences observed in DT gait speeds highlight the need for integrating cognitive assessments into frailty screening protocols, supporting timely interventions to improve health outcomes.